Archaeological narratives of the North American Great Plains: from ancient pasts to historic resettlement - Trabert, Sarah J., author; Hollenback, Kacy L., author; The SAA Press, publisher (Colorado State University. Libraries, 2021)
Stretching from Canada to Texas and the foothills of the Rockies to the Mississippi River, the North American Great Plains have a complex and ancient history. The region has been home to Native peoples for at least 16,000 years. This volume is a synthesis of what is known about the Great Plains from an archaeological perspective, but it also highlights Indigenous knowledge, viewpoints, and concerns for a more holistic understanding of both ancient and more recent pasts. Written for readers unfamiliar with archaeology in the region, the book emphasizes connections between past peoples and contemporary Indigenous nations, highlighting not only the history of the area but also new theoretical understandings that move beyond culture history. This overview illustrates the importance of the Plains in studies of exchange, migration, conflict, and sacred landscapes, as well as contact and colonialism in North America. In addition, the volume includes considerations of federal policies and legislation, as well as Indigenous social movements and protests over the last hundred years so that archaeologists can better situate Indigenous heritage, contemporary Indigenous concerns, and lasting legacies of colonialism today.--Provided by publisher.
Foundations of Contemporary Great Plains Archaeology -- The Ancient History of the Great Plains: Paleoindian and Archaic Lifeways -- Plains Woodland Regionalism and the Beginnings of Agriculture -- Homesteads, Hamlets, and Villages: Semi-Sedentary Agricultural Life -- Population Movement and Collective Stress: Dynamics In and Outside of Village Life -- (Peri)Colonialism: Indigenous Agency and Euro-American Entanglements -- Resettlement, War, Reservations, and Cultural Survivance -- Shifting Federal Policy, Heritage, and Contemporary Native Plains Nations.
Keywords: Indians of North America -- Great Plains -- Antiquities; Excavations (Archaeology) -- Great Plains; Great Plains -- Antiquities